2006
DOI: 10.1161/circulationaha.105.000505
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Regional but Not Global Contractile Function by the Direct Intramyocardial Autologous Bone Marrow Transplantation

Abstract: Background-Recent trials have shown that intracoronary infusion of bone marrow cells (BMCs) improves functional recovery after acute myocardial infarction. However, whether this treatment is effective in heart failure as a consequence of remodeling after organized infarcts remains unclear. In this randomized trial, we assessed the hypothesis that direct intramyocardial injection of autologous mononuclear bone marrow cells during coronary artery bypass graft (CABG) could improve global and regional left ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(148 citation statements)
references
References 26 publications
6
134
0
8
Order By: Relevance
“…The second important disadvantage of BMSC is that the proliferation and differentiation capacity of MSC declines with age, reducing their therapeutic potential (Stolzing et al 2008). Additionally, low frequency of mesenchymal stem cell creates a threat for cell migration and engraftment (Kuethe et al 2004;Wagner et al 2005;Hendrikx et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The second important disadvantage of BMSC is that the proliferation and differentiation capacity of MSC declines with age, reducing their therapeutic potential (Stolzing et al 2008). Additionally, low frequency of mesenchymal stem cell creates a threat for cell migration and engraftment (Kuethe et al 2004;Wagner et al 2005;Hendrikx et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…5,6) Different bone marrow cells types have been used commonly after selection and cultivation. 10,11) CD133 + cells were probably most frequently used and proofed to be efficient. However, preparation of these cells is very time and cost intensive.…”
Section: Discussionmentioning
confidence: 99%
“…79 Some trials did not show significant results, 76,85 while others demonstrated benefits, but no effect on EF. 66,67,74,77,80,84,86 A highly anticipated trial, FOCUS-CCTRN, assessed BMC via transendocardial injection in chronic HF. However, results indicated no significant change in endpoints.…”
Section: Clinical Outcomes Acute Myocardial Infarctionmentioning
confidence: 99%